2022
DOI: 10.1111/nph.18390
|View full text |Cite
|
Sign up to set email alerts
|

Finding new friends and revisiting old ones – how plant lipid droplets connect with other subcellular structures

Abstract: unster, 48143 M€ unster, Germany Contents Summary 833 I. Lipid droplet functions and composition 833 II. Lipid droplet-endoplasmic reticulum connections in plant cells 834 III. Lipid droplet-peroxisome connections in plant cells 836 IV. Lipid droplet-plasma membrane connections in plant cells 836 V. Conclusions 837 Acknowledgements 837 References 837

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Two steroleosin isoforms were detected in tubers (Figure S5b). Interestingly, seed lipid droplet protein (SLDP), another LD‐associated protein (Kretzschmar et al., 2020) that is seed‐ and seedling‐specific in Arabidopsis (Klepikova et al., 2016) and is part of a membrane contact site between LDs and the plasma membrane (Krawczyk et al., 2022; Scholz et al., 2022), was also detected in tubers.…”
Section: Resultsmentioning
confidence: 99%
“…Two steroleosin isoforms were detected in tubers (Figure S5b). Interestingly, seed lipid droplet protein (SLDP), another LD‐associated protein (Kretzschmar et al., 2020) that is seed‐ and seedling‐specific in Arabidopsis (Klepikova et al., 2016) and is part of a membrane contact site between LDs and the plasma membrane (Krawczyk et al., 2022; Scholz et al., 2022), was also detected in tubers.…”
Section: Resultsmentioning
confidence: 99%
“…Further, consistent with the close relationship between peroxisomes and mitochondria, recent studies have shown peroxisomal de novo biogenesis from mitochondria [ 27 , 43 46 ]. Peroxisomes are also associated with lipid bodies in different experimental models [ 24 26 , 47 ]. Moreover, Bartz et al showed the presence of bidirectional lipid trafficking between peroxisomes and lipid bodies [ 23 ], suggesting coordinated regulation of lipid metabolism and energy balance by peroxisomes and lipid bodies [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a note, the lipid droplets mentioned here in this study are not what had been described as “oil body” in liverworts. Lipid droplets are present in almost all green plants accumulating compounds that are not soluble in the aqueous phase, and oil bodies are present only in liverwort, storing large quantities of toxic sesquiterpenoids [ 17 , 52 , 53 , 54 , 55 ]. Lipid droplets are subcellular organelles of monolayer membranes with a diameter of about 0.5–2 µm, while oil bodies are an endocrine structure surrounded by a lipid bilayer membrane [ 13 , 55 ].…”
Section: Discussionmentioning
confidence: 99%